Population structure in genome-wide association studies - Davison, Dan (Henry Stewart Talks, 2008)
What is population structure?, The problem of structure in association studies, Detecting unknown structure, Mixture modelling, principal components analysis, Is there a problem?, Controlling for known structure: matching, family-based designs, stratified testing, Controlling for unknown structure: genomic control, mixture modelling, principal components, regression modelling
Archived at 2025/02/06